2009
DOI: 10.1139/e09-041
|View full text |Cite
|
Sign up to set email alerts
|

Eocene and Neogene volcanic rocks in the southeastern Nechako Basin, British Columbia: interpretation of the Canadian Hunter seismic reflection surveys using first-arrival tomography

Abstract: Geological investigation of the near-surface in the southeastern Nechako Basin is difficult. Shallow seismic reflection imaging is poor due in part to an extensive cover of Eocene and Neogene volcanic rocks. Outcrops of these volcanic rocks, and the primarily Cretaceous bedrock, are commonly obscured by Quaternary deposits and vegetation. Estimates of near-surface P-wave velocity are derived from the tomographic inversion of seismic first-arrivals, an effective tool when seismic imaging is poor. Tomographic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…If originally deposited, the preservation of any Cretaceous sedimentary strata beneath these Tertiary rocks would depend on the level of erosion prior to Tertiary crustal extension. Hayward and Calvert (2009) found that Chilcotin Group volcanic rocks are characterized by unusually low velocities of 1.6-3.6 km/s in tomographic velocity models derived from the firstarrival tomography of short, <2.5 km, offset reflection lines shot by Canadian Hunter Ltd. Our results are consistent with their finding because we infer velocities of 1.4-3.6 km/s close to the surface where the surface lithology is identified as Chilcotin Group. However, laboratory velocity measurements on dry samples cored from massive flows of Chilcotin basalt yield velocities of 3.9-6.3 km/s with a mean of 4.8 km/s (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…If originally deposited, the preservation of any Cretaceous sedimentary strata beneath these Tertiary rocks would depend on the level of erosion prior to Tertiary crustal extension. Hayward and Calvert (2009) found that Chilcotin Group volcanic rocks are characterized by unusually low velocities of 1.6-3.6 km/s in tomographic velocity models derived from the firstarrival tomography of short, <2.5 km, offset reflection lines shot by Canadian Hunter Ltd. Our results are consistent with their finding because we infer velocities of 1.4-3.6 km/s close to the surface where the surface lithology is identified as Chilcotin Group. However, laboratory velocity measurements on dry samples cored from massive flows of Chilcotin basalt yield velocities of 3.9-6.3 km/s with a mean of 4.8 km/s (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The significant overlap in P-wave velocity (3.6-5.3 km/s) between the Eocene Ootsa Lake and Cretaceous Taylor Creek groups indicates that they could be difficult to discriminate using P-wave velocity alone. The measured P-wave velocities of cores from Chilcotin volcanic rocks range from 3.94 to 6.28 km/s, and as noted previously by Hayward and Calvert (2009), these values are significantly greater than seismic velocities estimated at a larger scale in the field using seismic refraction tomography.…”
Section: Sonic Log and Laboratory Velocity Measurementssupporting
confidence: 67%
See 1 more Smart Citation
“…The Nechako Basin, also an interior basin located in British Columbia, covers 75,000 km 2 . Because it is overlain by volcanic flows, less is known about the sedimentary structure, but sediment thickness is estimated to be ∼3 km in some places [e.g., Hayward and Calvert, 2009;Calvert and Hayward, 2009].…”
Section: Tectonic Settingmentioning
confidence: 99%
“…5a). Although such low velocities are not typically associated with volcanic rocks (values determined from core samples are commonly 4.0-6.5 km/s), first arrival tomography across the Nechako-Chilcotin plateau found velocities of 1.8-3.0 km/s associated with the Miocene-Pliocene Chilcotin volcanics (Hayward and Calvert 2009;Talinga and Calvert 2014). The explanation for such low velocities is unclear, but could be related to the presence of a variety of high porosity volcanic facies, which may in some cases occur above the water table.…”
Section: Tomographic Velocity Modelsmentioning
confidence: 96%